miR-532-5p promotes breast cancer proliferation and migration by targeting RERG - Huang, Lei (Exp Ther Med, 2020)
Aberrant expression of microRNAs (miRNAs/miRs) mediates the initiation and progression of breast cancer. Therefore, it is important to investigate the molecular mechanisms of miRNAs and their effects on breast cancer progression. In the present study, miR-532-5p was highly expressed in breast cancer tissues compared with normal tissues. In addition, expression of ras-related and estrogen-regulated growth inhibitor (RERG), a tumor suppressor in breast cancer, was negatively correlated with miR-532-5p expression. Inhibition of miR-532-5p significantly elevated RERG at both mRNA and protein levels and inactivated the mitogen-activated protein kinase (MAPK)/ERK signaling pathway. Overexpression of miR-532-5p decreased RERG expression and activated the MAPK/ERK signaling in breast cancer cell line MDA-MB-231. Bioinformatic analysis indicated that RERG 3′-untraslated region contained a putative binding site for miR-532-5p. Dual luciferase assay further validated RERG as a target gene of miR-532-5p. Notably, downregulation of miR-532-5p inhibited MDA-MB-231 cell proliferation and migration, which was partially attenuated upon RERG knockdown. In conclusion, the current study revealed an oncogenic role of miR-532-5p in breast cancer cells via direct targeting of RERG expression.